Increased proportion of physical child abuse injuries at a level I pediatric trauma center during the Covid-19 pandemic. (June 2021) - Kovler, Mark L.; Ziegfeld, Susan; Ryan, Leticia M.; Goldstein, Mitchell A.; Gardner, Rebecca; Garcia, Alejandro V.; Nasr, Isam W.
Highlights: Social distancing orders have been justifiably required to slow the spread of the Covid-19 pandemic. Little is known regarding the secondary health consequences of these mandates. There was an increased proportion of physical child abuse injuries at our level I pediatric trauma center during the Covid-19 pandemic. Heightened awareness of this unintended consequence of social distancing can help to protect vulnerable children. Abstract: Background and objectives: The Covid-19 pandemic has forced mass closures of childcare facilities and schools. While these measures are necessary to slow virus transmission, little is known regarding the secondary health consequences of social distancing. The purpose of this study is to assess the proportion of injuries secondary to physical child abuse (PCA) at a level I pediatric trauma center during the Covid-19 pandemic. Methods: A retrospective review of patients at our center was conducted to identify injuries caused by PCA in the month following the statewide closure of childcare facilities in Maryland. The proportion of PCA patients treated during the Covid-19 era were compared to the corresponding period in the preceding two years by Fisher's exact test. Demographics, injury profiles, and outcomes were described for each period. Results: Eight patients with PCA injuries were treated during the Covid-19 period (13 % of total trauma patients), compared to four in 2019 (4 %, p < 0.05) and three in 2018 (3 %, p < 0.05). The median age of patients in the Covid-19 period was 11.5 months (IQR 6.8–24.5). Most patients were black (75 %) with public health insurance (75 %). All injuries were caused by blunt trauma, resulting in scalp/face contusions (63 %), skull fractures (50 %), intracranial hemorrhage (38 %), and long bone fractures (25 %). Conclusions: There was an increase in the proportion of traumatic injuries caused by physical child abuse at our center during the Covid-19 pandemic. Strategies to mitigate this secondary effect of social distancing should be thoughtfully implemented.